Risk Bearing Ability: Determinants of Climate Change Resilience among the Most Vulnerable Small Holder Coconut Planter Communities in Kurunegala District - Umashankar, K.; Dissanayake, P.C.D.A. (Sri Lanka Agricultural Economics Association, 2019)
Small holder coconut cultivators, which accounts for 99% of the market share, with their limited resources and small levels of production tend to bear adverse effect of the climate change. The effect of climate change eventually impacts consumer welfare and the food security of the country. Therefore it is imperative to understand the indicators of resilience in the small-holder coconut farmers. Three Divisional Secretariat Divisions which have been identified as highly vulnerable areas to climate change in plantation sector of Sri Lanka (Ministry of Environment of Sri Lanka; 2011) was selected for this study. Sample was defined as coconut farms with holding size of 2 acres-20 acres which are managed as family units. In drawing the sample, case purposive sampling was used while data was collected through an interviewer- distributed questionnaire. Climate change resilience of the community was considered as a function of the exogenous latent variables; Access to Basic Services (ABS), Adaptive Capacity (ADC), Assets (AST), Social Safety Nets (SSN) and Discrepancy (D). Observed variables were selected under each exogenous latent variable. The results indicated that the climate change resilience of the selected community to be statistically affected by the latent endogenous variables; Among the variables tested 22 variables came across as indicative of climate change resilience of the target group; education level of the household head (edu), subjective access of famers to education (sed), assistance during crisis (adc), extent of coconut cultivation (cln), number of trees per holding (nct), rented land ownership (rln), diversity of income sources (dis) and number of family members involved in farm activities (nff) were shown to have a statistically significant positive relationship with resilience at 99% confidence level. Access to internet (int), assistance from cooperative societies (acp) and the climate effect mitigation techniques (cem) had a positive effect on resilience at 95% confidence level. Frequency of extension services (fex), subjective access to extension (sbe), access to information (inf) and livestock/ poultry integration (lah) were found to be positively affects resilience at confidence level of 90%.
Keywords: Access to basic services; Adaptive capacity; Assets; Discrepancy; Social safety networks